The Wide and Unpredictable Scope of Synthetic Cannabinoids Toxicity - Jose Orsini; Christa Blaak; Eric Tam; Salil Rajayer; Joaquin Morante; Angela Yeh; Ashvin Butala (Case Reports in Critical Care)
Drug use and abuse continue to be a large public health concern worldwide. Over the past decade, novel or atypical drugs have emerged and become increasingly popular. In the recent past, compounds similar to tetrahydrocannabinoid (THC), the active ingredient of marijuana, have been synthetically produced and offered commercially as legal substances. Since the initial communications of their abuse in 2008, few case reports have been published illustrating the misuse of these substances with signs and symptoms of intoxication. Even though synthetic cannabinoids have been restricted, they are still readily available across USA and their use has been dramatically increasing, with a concomitant increment in reports to poison control centers and emergency department (ED) visits. We describe a case of acute hypoxemic/hypercapnic respiratory failure as a consequence of acute congestive heart failure (CHF) developed from myocardial stunning resulting from a non-ST-segment elevation myocardial infarction (MI) following the consumption of synthetic cannabinoids.